1994
DOI: 10.2331/fishsci.60.563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Larval Settlement of the Barnacle <i>Balanus amphitrite</i> Reared in the Laboratory

Abstract: The effects of environmental factors such as light illumination , black and white substrates, salinity, temperature and hydrostatic pressure on larval settlement of the reared barnacle Balanus amphitrite were examined. Settlement was found to be sensitive to the light intensity and color of substrates, and was observed over a wide range of salinity. temnerature and hydrostatic pressnre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Intertidal barnacles as conspicuous, widely distributed, and ecologically important species have served to study the eVects of environmental factors, e.g., temperature, salinity, food type and concentration, light (e.g., Crisp and Ritz 1973;Harms 1984;Holm 1990;Konya and Miki 1994;Anil et al 1995Anil et al , 2001Anil and Kurian 1996;Qian 1997, 1999;Hentschel and Emlet 2000;Thiyagarajan et al 2002a;Nasrolahi et al 2007), and more recently global warming and ocean acidiWcation (Findlay et al 2008;Hung et al 2008;Findlay et al 2009;McDonald et al 2009;Wong et al, in press) on larval development and settlement success. Much of this progress on what is frequently considered the most sensitive life history phase is facilitated because barnacle larvae can be easily reared under controlled conditions (Thiyagarajan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Intertidal barnacles as conspicuous, widely distributed, and ecologically important species have served to study the eVects of environmental factors, e.g., temperature, salinity, food type and concentration, light (e.g., Crisp and Ritz 1973;Harms 1984;Holm 1990;Konya and Miki 1994;Anil et al 1995Anil et al , 2001Anil and Kurian 1996;Qian 1997, 1999;Hentschel and Emlet 2000;Thiyagarajan et al 2002a;Nasrolahi et al 2007), and more recently global warming and ocean acidiWcation (Findlay et al 2008;Hung et al 2008;Findlay et al 2009;McDonald et al 2009;Wong et al, in press) on larval development and settlement success. Much of this progress on what is frequently considered the most sensitive life history phase is facilitated because barnacle larvae can be easily reared under controlled conditions (Thiyagarajan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cyprid locomotion, exploration and settlement has been well documented (Knight-Jones 1953;Crisp 1983;Yule and Crisp 1983;Crisp 1985;Crisp 1990;Mullineaux and Butman 1991;Glenner and Hoeg 1993;Konya and Miki 1994;Miron et al 2000;Dahlstrom et al 2004) use their antennae to "walk" along a substrate until a suitable location is found to settle. Faimali et al (2004) found that barnacle cyprids may perceive signals about the substratum surface or its biofilm, which plays a role in their settlement preference.…”
Section: Barnacles: Intriguing Underwater Adhesionmentioning
confidence: 99%
“…Results from this study underline the importance of testing coatings within conditions they will be facing when commercially utilized. (Prosser et al 1991;Callow et al 2007) 2.4.2 Genetic relationship and CRS Past and current research has shown how differing environmental factors such as flow force and temperature, give rise to phenotypic plasticity in barnacles (Konya and Miki 1994;Anil et al 2001;Marchinko 2003;Li and Denny 2004). The degree to which phenotypic or functional variation is expressed within a population is ultimately dependant on the genetic connectivity of the organisms.…”
Section: Temperature Effects On Critical Removal Stressmentioning
confidence: 99%
See 2 more Smart Citations